2017
DOI: 10.1080/10790268.2017.1390644
|View full text |Cite
|
Sign up to set email alerts
|

Walking speed is not the best outcome to evaluate the effect of robotic assisted gait training in people with motor incomplete Spinal Cord Injury: A Systematic Review with meta-analysis

Abstract: Context While there are previous systematic reviews on the effectiveness of the use of robotic-assisted gait training (RAGT) in people with spinal cord injuries (SCI), as this is a dynamic field, new studies have been produced that are now incorporated on this systematic review (SR) with meta-analysis, updating the available evidence on this area. Objective To synthesise the available evidence on the use of RAGT, to improve gait, strength and functioning. Methods SR and meta-analysis following the Cochrane Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 58 publications
(165 reference statements)
0
15
0
Order By: Relevance
“…The use of robot-assisted gait training (RAGT) in the field of rehabilitation has become more widespread since this training is not limited by the individuals' muscle paralysis level. Current systems of RAGT include Lokomat (Hocoma AG, Switzerland), G-EO systemTM (Reha Technology AG, Switzerland), Walkbot (P&S Mechanics Co., Ltd, Korea), and ReoAmbula-torTM (Motorika, USA Inc.) [22]. RAGT provides repetitive and functional task training which induces greater activation of the sensorimotor cortex (S1, S2) and cerebellar regions [23].…”
Section: Introductionmentioning
confidence: 99%
“…The use of robot-assisted gait training (RAGT) in the field of rehabilitation has become more widespread since this training is not limited by the individuals' muscle paralysis level. Current systems of RAGT include Lokomat (Hocoma AG, Switzerland), G-EO systemTM (Reha Technology AG, Switzerland), Walkbot (P&S Mechanics Co., Ltd, Korea), and ReoAmbula-torTM (Motorika, USA Inc.) [22]. RAGT provides repetitive and functional task training which induces greater activation of the sensorimotor cortex (S1, S2) and cerebellar regions [23].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies on RAGT in SCI patients, the 6mWT, WISCI-II, and LEMS revealed improvements compared to the control group; however, the 10 MWT and BBS showed no significant improvement after the RAGT. [7,9,15,[20][21][22] Most studies on RAGT in SCI patients used the 10MWT, 6mWT, LEMS, and WISCI-II as clinical outcomes. Only one study has used BBS as a clinical outcome [21], and no study has assessed proprioception in RAGT studies in SCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…RAGT in patients with incomplete SCI revealed improvements in mobility-related outcomes (gait endurance and Walking Index for Spinal Cord Injury [WISCI]-II) and lower extremity motor strength compared to conventional physiotherapy [7,9,12]. However, recent RAGT studies for incomplete SCI patients have used Lokomat ® , except for three articles [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that high walking speed is important for daily living and social participation ability, 32 and that walking quality includes the ability to walk quickly. 33 Some walking training methods aim to improve walking speed. 34 Taken together, these findings suggest that walking under ETAAC conditions could improve walking quality and facilitate walking in daily living.…”
Section: Discussionmentioning
confidence: 99%